Role of procalcitonin levels on COVID-19 patients at Siti Fatimah hospital south Sumatera - Nurhayati,; Asrori,; Edyansyah, Erwin; Mutholib, Abdul; Hermansyah, Herry; Irham, Afifah (International Journal of Research in Medical Sciences, 2023)
Background: COVID-19 is a systemic disease that affects a broad spectrum of tissues and cells. Infected patients experience a wide variety of clinical signs, ranging from mild clinical signs to bilateral interstitial pneumonia. COVID-19 patients who also experience acute respiratory distress syndrome can result in multi-organ failure without comorbidities. Procalcitonin (PCT) also indicates severity and prognosis to reduce mortality. Method: The research method is descriptive with a cross-sectional approach. The research was conducted at the Siti Fatimah hospital in South Sumatra province in February to May 2022. The sample for this research was the results of a PCT examination in 2021 totaling 66 people. The method for examining PCT levels uses the enzyme-linked method with serum or plasma samples. Results: Obtained PCT levels showed that there was a low risk of PCT levels (≥0.05-<0.5) in 26 patients (39.4%), severe risk of PCT levels (≥0.5-<2) in 15 patients (22 .7%) and high risk of PCT levels (≥2) in 25 patients (37.9%). Based on mortality status, high levels were obtained in 43 patients with a low-risk living category in 21 patients. Based on the history of the disease, high levels were obtained in 41 patients with a history of high-risk disease in 18 patients. Based on the category of treatment in the inpatient room, high levels were obtained in 37 patients treated in the non-ICU room, resulting in low-risk PCT levels in 17 patients. Conclusions: There is a 39.4% PCT level (≥0.05-<0.5) which indicates low risk is more common in COVID-19 patients than severe risk and high risk.